Adaptasi Berbasis Budaya dan Sosial Masyarakat (Studi Kasus Etnis Tionghoa di Kota Palembang) - Nursapia Harahap (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2020)
Adaptation depends on the structure or physical behavior of an individual that increases his ability to survive in his habitat. Whatever helps him survive in the environment he occupies includes the cultural and social community. Remembering adaptation refers to the ability to adapt to various conditions in their environment. This study aims to analyze the cultural adaptation and social adaptation of ethnic Chinese communities in theory and practice. Then clarify the important role that culture plays in enabling adaptation, and show how community-based cultural and social adaptation is well placed. Besides that it also measures the typical starting point of good community development by emphasizing community participation, kinship systems, individual welfare, culture, community and adaptation. For this reason, in particular this research relies on thoughts that have emerged from observations about the cultural and social role of society in individual lives. The results of this study indicate that the Chinese ethnic has been able to adapt to the cultural and social adaptation of the community well in the city of Palembang. This ability can be seen from the socio-economic life, society and culture of ethnic Chinese who are able to survive with the capital of developing business ventures and working in the political field. In addition, the Chinese are also able to adapt structurally and culturally by following the cultural and community development of Palembang City.kkan